The Effect of Sovereign Debt on Economic Growth: The Case of Oil-Rich Countries - Salameh, Hussein; Alodadi, Ahmed; Alzubi, Khaled (International Journal of Economics and Financial Issues, 2020)
Key studies have identified the need to study the role of sovereign debt on economic growth, particularly in relation to countries with heavily oil-based status economies. This paper applies a panel vector autoregressive approach to examine the impact of sovereign debt on economic prosperity in several oil-rich countries between 2002 and 2017. The results show that in oil countries, like other developing countries, government debt has not had a positive impact on enhancing economic growth, resulting in a reluctance of such countries to invest debts in production, and a desire for the type of diversification of sources of income observable in most advanced countries. Keywords: Co-integration, Sovereign Debt, Oil-rich Countries JEL Classifications: A10, B22, B23, E23, E52, E62 DOI: https://doi.org/10.32479/ijefi.9120